1996
DOI: 10.1021/je960124k
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Various Alkali Metal and Alkaline Earth Metal Compounds in Methanol

Abstract: Solubilities of the halides, nitrates, carbonates, sulfates, and some perchlorates of all the alkali metals and alkaline earth metals in methanol at room temperature have been determined. Data on some, such as cesium and rubidium fluoride, nitrate, carbonate, and sulfate, appear to be reported for the first time. Comparison with earlier results from the literature reveals a number of discrepancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 15 publications
1
33
1
Order By: Relevance
“…First, NaI has higher solubility in the solvent mixture. The solubility of NaI in methanol is 78% to 83% at 258C, 69 which is much higher than that of sodium chloride (1.4% at 258C) 69 and sodium acetate (<2.4% in 98.4% aqueous methanol at 8-198C). 70 Since methanol is more polar than chloroform, the solubility of the additive salts in the chloroform/methanol mixture is most likely lower than in methanol alone.…”
Section: Nai Additive For Highly Sensitive Esi-ms Detection Of Intactmentioning
confidence: 93%
“…First, NaI has higher solubility in the solvent mixture. The solubility of NaI in methanol is 78% to 83% at 258C, 69 which is much higher than that of sodium chloride (1.4% at 258C) 69 and sodium acetate (<2.4% in 98.4% aqueous methanol at 8-198C). 70 Since methanol is more polar than chloroform, the solubility of the additive salts in the chloroform/methanol mixture is most likely lower than in methanol alone.…”
Section: Nai Additive For Highly Sensitive Esi-ms Detection Of Intactmentioning
confidence: 93%
“…For binary systems, it is possible to determine the influence of temperature on the solubility, but discrepancies like those shown in figure 1 are usually detected. (15,16) Thus, if the solubility of a salt is needed, even for the most common solvents like methanol or ethanol, reliable information is usually not available, but luckily some rare comprehensive studies like the one by Stenger (17) may be found. Stenger (17) published the data for solubility of several salts in methanol at T = 298.15 K, and concluded that some experimental determinations should be carried out either to check some values or to provide new information.…”
Section: Experimental Workmentioning
confidence: 99%
“…For this reason, it has one of the shortest anion-cation distance and hence high lattice energy (1036 kJ mol −1 ). As the solvation of the ions generally does not balance the lattice energy, LiF is only slightly soluble in water (0.027 g/100 g at 291.15 K [1]), or in other protic solvents like methanol [2] and almost insoluble in propanone. Hence, LiF crystals, which possess the highest UV transmission of any material, can be cleaned with alcohol.…”
Section: Introductionmentioning
confidence: 99%